Pomegranate Protects Minocycline Induced Epidermal Pigmentation in the Extremities of Guinea Pigs (Medical Forum Monthly, 2024)
Objective: To investigate the protective effects of Pomegranate on Minocycline induced epidermal pigmentation on the extremities of guinea pigs.Study Design: An experimental observational study.Place and Duration of Study: This study was conducted at the Anatomy Department, BMSI, J PMC, Karachi.Materials and Methods: 60 adult guinea pigs were divided into 3 groups A B and C, A served as control, B given Minocycline, while C given Minocycline with Pomegranate for 8 weeks, after which their skin was processed for histological examination and pigmentation was observed in Masson Fontana stained sections under light microscope.Results: The melanin pigmentation deposition observed in Minocycline treated group B, distributed densely and extended till stratum corneum as compared to the control group A, while in the Pomegranate treated group C along with Minocycline, the melanin pigmentation was considerably reduced and was observed to be distributed sparsely extended till stratum spinosum. Conclusion: Based on the present study it is conducted that pigmentary changes induced by Minocycline can be protected by taking pomegranate.